Uporaba analizatorja debeline mrežnice pri boleznih mrežnice in glavkomu - Cvenkel, Barbara (Zdravniški vestnik, 2004)
Background. A change in retinal thickness caused by several ocular diseases can be measured quantitatively by the retinal thickness analyser (RTA). The principle of RTA is based on projecting a laser slit (540 nm) onto the retina and viewing its intersection with the retina. The separation between the reflections from the vitreoretinal and the chorioretinal interface is a measure of the retinal thickness. By scanning the posterior pole and/or peripapillary retina, the intersections of the laser slit with the retina are presented as multiple optical cross sections and as colour-coded retinal thickness maps. Conclusions. In the article the application of the new method in glaucoma and other retinal diseases is presented. Scanning RTA is a non-invasive method and provides quantitative information that may be useful in the diagnosis and monitoring of glaucoma and a variety of retinal diseases in clinical practice.
Keywords: Anatomy And Histology; Diabetic Retinopathy; Diabetična retinopatija; diagnostika; Glaucoma; Glavkom; Macular Edema, Cystoid; Makularni edem cistoidni; Microscopy, Confocal; Mikroskopija konfokalna; Mrežnica; Mrežnica, bolezni; Mrežnica, perforacija; očesne bolezni; Pathology; Retina; Retinal Diseases; Retinal Perforations